Investigation of PML Decay Function Performance and its Application in Radiation Boundary of Dam Reservoir - S. Pirboudaghi , M.H. Ahmadi , A. Nas, Gh. Saeedifar, (International Journal of Scientific Research and Management (IJSRM), 2015)
The estimation of precise hydrodynamic forces on dam faces due to earthquakes is an important aspect of the analysis and design of dams. A key issue in the earthquake analysis of this kind of coupled systems is the accurate and inexpensive dynamic modeling of the unbounded reservoir. A suitable boundary condition should be applied along the truncation surface. Sommerfeld boundary condition is the most common traditionally used approach with enough large distance from the dam to obtain accurate results. Other approach to such modeling uses a bounded domain surrounded by an absorbing boundary or layer that absorbs waves propagating outwards from the bounded domain. A perfectly matched layer (PML) is an absorbing layer model for linear wave equations that absorbs, almost perfectly, propagating wave of all non-tangential angels of incidence and of all non-zero frequencies. In this research a finite element program is developed in order to do the seismic analysis of dam-reservoir systems, and the PML boundary condition is adopted as a truncation boundary condition for timeharmonic dam-reservoir interaction. The results obtained from this analysis are compared with the results of the same system but with Hyper elements as exact solution in accuracy. Parametric analysis of the coupled system with different parameters of the PML is done and some useful rules are obtained in order to introduce PML decay function. Results from this problem demonstrate the high accuracy achievable by PML models using small bounded domains and at low computational costs.